( Analysis for Equilibrium Moisture Content, Sorption-Isotherm and Economic Analysis of Ginger Powder Processing (Zingiber officinale Rosc)) - Rizal Alamsyah; Bambang Irawan; Putiati Mahdar (Warta Industri Hasil Pertanian, 2005)
A study to analyse for equilibrium moinsture content, sorption-isotherm and economic analysis of ginger powder processing (zingiber officinalle Rosc) production has been conducted. the study was aimed at designing adsorption and desorption model of ginger powder by investigating its equilibrium moisture content conducted at 30 C and 40 C, relative humifily (Rh)level of 11.3, 32.4, 51.4, 63.5, and 75.0% for adsorption model and 11.2, 31.8, 48.5, 61.4 and 75.8% for desorption model. Four models of smith, henderson, caurie and bradley were emploved and modified to investigate a model which appropriate for ginger powder composition. before resulting the models and curves. it was initially calculated some constant. the modification of smith model showed the best result for adsorption condition. Financial analysis was conducted to evaluated the financial viability of ginger powder processing. the financial analysis of ginger production of 500 kg per day consits of some parameter e.g IRR (internal rate return) was 28.53%, NPV (net present value) was Rp. 204.252.000.-, net revenue was Rp. 252.000.000,- and PBB (pay back period) was 3.5 years. It can be concluded that ginger powder production was viable to be set up.